Indonesian Question Answering System for Factoid Questions using Face Beauty Products Knowledge Graph - Mahanti Indah Rahajeng; Ayu Purwarianti (Indonesia Association of Computational Linguistics (INACL), 2021)
Question answering (QA) system is developed to find the right answers from natural language questions. QA systems can be used for building chatbots or even search engines. In this study, we’ve built an Indonesian QA system that uses Anindya Knowledge Graph as its data source. The idea behind this QA system is translating questions into SPARQL queries. The proposed solution consists of four modules, namely question classification, information extraction, token mapping, and query construction. The question classification and the information extraction modules were experimented using SVM, LSTM, and fine-tuning IndoBERT. The text representations were also tested to find the best result among tf-idf, FastText, and IndoBERT. In our experiment, we found that the fine-tuning IndoBERT model had obtained the best performance on both question classification and information extraction modules.